Exploring the effects of Chinese herbal ingredients on the signaling pathway of alopecia and the screening of effective Chinese herbal compounds. (10th August 2022) - Dou, jinjin; Zhang, Zhiming; Xu, Xianrong; Zhang, Xiwu
Abstract: Ethnopharmacological relevance: alopecia is a hair disorder that can add a significant medical and psychological burden to patients. Currently, the FDA-approved drugs for the treatment of androgenetic alopecia (AGA) are minoxidil and finasteride and immunosuppressives are therapeutic options for alopecia areata (AA), but the objective adverse effects and high cost of these treatments reduce patient compliance and thus the effectiveness of the drugs. Traditional Chinese medicine (TCM) has good efficacy, a high safety profile and low treatment costs, but its mechanism of action is still not fully understood. The use of signaling pathways to modulate hair loss is a major direction in the study of the pathogenesis and pharmacology of alopecia. Aim of the study: This review aims to collect the results of experimental studies related to alopecia, to screen previously documented combinations of herbs claimed to be effective based on the herbs and their constituent compounds used in the identified studies, and to uncover other useful information that we hope will better guide the clinical application and scientific research of drug combinations or individual herbs for the treatment of alopecia. Materials and methods: We have reviewed experimental studies to determine the methods used and the mechanisms of action of the herbs and constituent compounds. The following keywords were searched in databases, including PubMed, EMBASE, CNKI and CSTJ." Medicinal plants" "Chinese herbal medicine", "hair loss", " alopecia", "androgenetic alopecia" and " alopecia areata ". We also collected combinations of drugs from books approved by various schools for screening. Results: Using known combinations of compounds within herbal medicine to match the documented combinations, 34 topical combinations and 74 oral combinations were identified, and among the 108 herbal combinations screened Angelica, Rehmannia glutinosaLigusticum chuanxiong hort, Radix Rehmanniae, etc. The number of occurrences was very high, and the association with vascular drugs was also found to be very close. Conclusions: This review further elucidates the therapeutic mechanisms of the compounds within the herbal components associated with alopecia and screens for other combinations that may be dominated by this component for the treatment of alopecia, uncovering compounds from other drugs that may be key factors in the treatment of alopecia. This improvement will provide a better quality of evidence for the effectiveness of herbs and compounds used to treat alopecia. Graphical abstract: Image 1 Highlights: In addition to androgenic pathway, other pathways can lead to hair loss, creating symptoms similar to androgenetic alopecia. Compounds within traditional herbal medicine can promote hair growth in animal or cellular models of hair loss. Herbs that have not been shown to be effective in hair loss appear more frequently in prescriptions than effective ones. Illicium anisatum Gaertn. Constituents are used topically for hair loss or may be inactivated by the digestive tract.